The Effectiveness of Problem-Based Learning Group Guidance with Dakon Game in Reducing Student Burnout - Ristiawan, Hendri; Khan, Rosa Imani; Milasanty, Devi Asmindra (Asa Jurnal Penelitian Pendidikan dan Pembelajaran, 2025)
This study investigates the effectiveness of group counseling integrating Problem-Based Learning (PBL) with the traditional Indonesian Dakon game to reduce academic burnout among five high-burnout students in Class XI-5 at SMAN 3 Kediri. Conducted through two cycles of classroom action research, the intervention combined PBL’s critical thinking and collaborative problem-solving with Dakon’s culturally relevant, interactive format, modified with reflective question cards addressing burnout causes and coping strategies. Data were collected via a 58-item burnout scale (Cronbach’s alpha = 0.87), observations, student reflections, and teacher evaluations, with validity ensured through triangulation, member checking, peer debriefing, and audit trails. Pre-intervention, all students exhibited high burnout. Post-Cycle I, 60% remained high, while 40% shifted to moderate. After Cycle II refinements, including contextualized questions and rewards, 60% reached moderate and 40% low burnout, with increased engagement and emotional resilience. The PBL-Dakon approach, rooted in cultural familiarity, fosters autonomy and social connection, aligning with Self-Determination Theory. Practically, it offers a cost-effective, replicable model for school counselors to address burnout, leveraging Indonesia’s cultural heritage to enhance student well-being.